Pengaruh Perilaku Orang Tua Terhadap Kepribadian Anak - Titin Triana (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Abstract: Devout children are children who believe in Allah, pious, like doing good and useful, as well as preventing themselves from evil deeds and dutiful to his parents. For that they need the guidance and coaching of targeted and programmed continuously ie from parents. Technically, the educational tools used are exemplary, advice, encouragement, praise, and habituation by using the steps in accordance with the development of child’s age. Keywords: child’s personality, behavior, education of children.